Performa Fasilitas Rumah Kompos Di Kabupaten Kendal, Jawa Tengah - Suhardono, Sapta; Sari, Mega Mutiara; Afifah, Anshah Silmi; Suryawan, I Wayan Koko (Journal of Sustainable Infrastructure, 2024)
Kendal District has two primary waste management facilities: the Pasar Kendal Composting House and the Jatirejo Composting House. This study meticulously evaluates the operational performance of these facilities throughout the 2021-2022 timeframe, uncovering a stark contrast in their waste processing achievements. In the year 2021, the Jatirejo facility managed to process only a paltry 0.35% of the total waste received, starkly juxtaposed against the Pasar Kendal facility, which impressively reduced 100% of its waste. The subsequent year, 2022, witnessed a dramatic shift in performance metrics: Jatirejo saw a significant uptick in its processing capacity to 50.00%, while Pasar Kendal experienced a reduction in efficiency, processing only 58.81% of its waste. This research accentuates the untapped potential for amplifying the capacity and effectiveness of composting as a waste management strategy in Kendal District, where a considerable volume of waste is composed of food remnants. The study proposes a series of solutions aimed at fortifying waste management capabilities, including infrastructure enhancement, comprehensive community education programs, and the enactment of more stringent governmental policies to facilitate improvement in waste processing rates.